The potential of fatty acid isotopes to trace trophic transfer in aquatic food-webs. (15th June 2020) - Burian, Alfred; Nielsen, Jens M.; Hansen, Thomas; Bermudez, Rafael; Winder, Monika
Abstract : Compound-specific isotope analyses (CSIA) of fatty acids (FA) constitute a promising tool for tracing energy flows in food-webs. However, past applications of FA-specific carbon isotope analyses have been restricted to a relatively coarse food-source separation and mainly quantified dietary contributions from different habitats. Our aim was to evaluate the potential of FA-CSIA to provide high-resolution data on within-system energy flows using algae and zooplankton as model organisms. First, we investigated the power of FA-CSIA to distinguish among four different algae groups, namely cyanobacteria, chlorophytes, haptophytes and diatoms. We found substantial within-group variation but also demonstrated that δ 13 C of several FA (e.g. 18:3 ω 3 or 18:4 ω 3) differed among taxa, resulting in group-specific isotopic fingerprints. Second, we assessed changes in FA isotope ratios with trophic transfer. Isotope fractionation was highly variable in daphnids and rotifers exposed to different food sources. Only δ 13 C of nutritionally valuable poly-unsaturated FA remained relatively constant, highlighting their potential as dietary tracers. The variability in fractionation was partly driven by the identity of food sources. Such systematic effects likely reflect the impact of dietary quality on consumers' metabolism and suggest that FA isotopes could be useful nutritional indicators in the field. Overall, our results reveal that the variability of FA isotope ratios provides a substantial challenge, but that FA-CSIA nevertheless have several promising applications in food-web ecology. This article is part of the theme issue 'The next horizons for lipids as 'trophic biomarkers': evidence and significance of consumer modification of dietary fatty acids'.